A Case of Subacute Cutaneous Lupus Erythematosus in a Patient with Mixed Connective Tissue Disease: Successful Treatment with Plasmapheresis and Rituximab - M. Fantò; S. Salemi; F. Socciarelli; A. Bartolazzi; G. A. Natale; I. Casorelli; A. Pavan; S. Vaglio; R. Di Rosa; R. D'Amelio (Case Reports in Rheumatology)
A 30-year-old woman affected by Mixed Connective Tissue Disease with scleroderma spectrum developed a facial eruption, a clinical and histological characteristic of subacute cutaneous lupus erythematosus (SCLE). Speckled anti-nuclear antibodies, high-titer anti-ribonucleoprotein1, anti-Sm, anti-Cardiolipin (aCL) IgG/IgM, and anti-Ro/SSA antibodies were positive. SCLE was resistant to Azathioprine, Hydroxychloroquine, and Methotrexate while Mycophenolate Mofetil was suspended due to side effects. Subsequently, the patient was treated with three cycles of therapeutic plasma exchange (TPE) followed, one month after the last TPE, by the anti-CD20 antibody Rituximab (RTX) (375 mg/m2 weekly for 4 weeks). Eight and 16 months later the patient received other two TPE and RTX cycles, respectively. This therapeutic approach has allowed to obtain a complete skin healing persistent even after 8-month follow-up. Moreover, mitigation of Raynaud's phenomenon, resolution of alopecia, and a decline of aCL IgG/IgM and anti-Ro/SSA antibodies were observed.